Proposal of a Model for Water Usage: Revenue Estimation in Brazil Hydrographic Basin - Sarmento Vieira, Allan; Fontgalland, Isabel (Technium Sustainability, 2023)
In order to improve the quality of aquatic ecosystems, a water collection instrument was established in the National Water Resources Policy (PNRH), with the purpose of collecting and allocating resources to the management of water systems, as well as stimulating the conscious and efficient use of water, with the direct finality of reducing the rates of waste and pollution of water sources. This instrument guided the definition of the objective from the present research, which is to estimate the collection of the Pianco-Piranhas-Açu Basin, located between the State of Paraiba and Rio Grande do Norte, to be calculated with a mathematical model of collection by the multiple water uses that consider volumes consumed, captured and for the discharge of effluents. To do so, it was analysed the main collection models adopted in Brazil to finally define the best algorithmic basis. Analysing the results, it was observed that the planned resources still do not provide a sustainable application of the real situation of the analysed basin, requiring further research to better understand the peculiarities of the region, given that the estimated collection is insufficient to provide the necessary infrastructure for Pianco-Piranhas-Açu (Brazil) river’s basin management system. Therefore, this situation serves to alert public water management bodies about the modelling to be used and the urgency of implementing the charging instrument, given that it could improve the quality of the hydrographic basin studied.